Seawater carbonate chemistry and skeleton-forming responses of reef-building corals under ocean acidification - Yixin Li; Hongwei Zhao; Yunpeng Zhao; Xin Liao; J Y Chen; Yanping Qin; Zuhong Lu; Yuehuan Zhang; Chunpeng He (PANGAEA, 2025)
Here, we studied the skeleton-forming strategies of 4 widely distributed coral species in a simulated acidified habitat with a pH of 7.6 to 7.8. We reconstructed and visualized the skeleton-forming process, quantified elemental calcium loss, and determined gene expression changes. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-09-01.